2015
DOI: 10.4103/0976-3147.153216
|View full text |Cite
|
Sign up to set email alerts
|

Identifying autonomic nervous system dysfunction in acute cerebrovascular attack by assessments of heart rate variability and catecholamine levels

Abstract: Objective:This study aimed to evaluate changes in the autonomic nervous system caused by cerebral lesions due to acute stroke. We assessed heart rate variability and catecholamine levels in lieu of stroke lesion localization.Materials and Methods:A total of 60 stroke patients and 31 healthy controls were enrolled in the study. Plasma epinephrine and norepinephrine levels were measured on the first, third, and seventh days following the stroke event. Heart rate variability was evaluated with time-domain and fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Our study data indicate the presence of a significant difference between the values of SBP, DBP and MAP between stroke patients and the control group, similar to the results of other authors (16). Patients with ischemic stroke and insular cortex damage present more often an increase of BP (17) and HR values, compared to those without involvement of the IC and those with left IC involvement.…”
Section: Discussionsupporting
confidence: 80%
“…Our study data indicate the presence of a significant difference between the values of SBP, DBP and MAP between stroke patients and the control group, similar to the results of other authors (16). Patients with ischemic stroke and insular cortex damage present more often an increase of BP (17) and HR values, compared to those without involvement of the IC and those with left IC involvement.…”
Section: Discussionsupporting
confidence: 80%
“… 3 , 16 However, the decrease in AC reflects a decrease in sympathetic activity, which is inconsistent with studies concluding that the sympathetic activity of stroke increased through the detection of catecholamine concentrations. 16 , 17 In the clinic, increased blood pressure, heart rate, and other characteristics of enhanced sympathetic activity are common in patients with cerebral infarction. In our study, we also found that R–R intervals of patients with infarction were shorter than those in controls, which might be a reflection of sympathetic hyperactivity.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the timepoint of 3 ​h post-stroke may be too acute for SNS dysregulation to be detected in the circulation. Indeed, a previous study showed plasma NA was elevated at 5 ​h following experimental stroke ( Smith et al., 1986 ), while others show an elevation after the first day in stroke patients ( Akıl et al., 2015 ; McCulloch et al., 2019 ). Additionally, the concentration of NA in the plasma is dependent on the rate of release and the rate of removal from the plasma whereby reduced removal of NA can increase detection of plasma NA without a change in SNS output ( Goldstein et al., 2003 ).…”
Section: Discussionmentioning
confidence: 95%
“…In light of new evidence showing a role for the SNS on immune regulation, we explored the effect of inhibiting β-adrenergic receptor on post-stroke outcomes. Indeed, plasma NA and other catecholamines are elevated in patients with stroke ( Akıl et al., 2015 ; McCulloch et al., 2017 ; Myers et al., 1981 ), thus the notion of NA-mediated post-stroke immune suppression is a possibility. In this study, we revealed stroke induced a systemic activation of the SNS as indicated by elevated levels of plasma catecholamines and UCP-1 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation